The Influence Work-Life Balance and Burnout on Job Satisfaction of Banking Industrial Employees in Pekanbaru City - Ade Irma Julianti; Desy Mardianty (PT Mattawang Mediatama Solution, 2024)
This research aims to test the effect of work-life balance and burnout on employee job satisfaction in the Pekanbaru city banking industry, both simultaneously and personally. This research is quantitative research. The sample in this study is a total of 100 employees of the banking industry in the city of Pekanbaru. The sampling technique used is saturated sampling by the way all populations are sampled. Data collection is by the primary method obtained from the results of the questionnaire distribution. The analysis technique used is multiple linear using the smartPLS version 3 application. Based on the results of research, it is shown that work-life balance (X1) has a positive and significant effect on Job Satisfaction (Y) and burnout (X2) has a positive and significant effect on job satisfaction (Y) in employees of the banking industry in the city of Pekanbaru. The three variables together work-life balance and burnout have a positive and significant effect on job satisfaction in employees in the banking industry in the city of Pekanbaru.